2011
DOI: 10.2351/1.3646907
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the bone repair in defects grafted with hydroxyapatite and collagen membrane combined with laser therapy in rats

Abstract: Bone regeneration is the result of cellular events such as osteogenesis and neovascularization. However, implantation of autogenous grafts may be necessary in cases of bone mass loss due to high impact trauma. The disadvantages of the latter approach include morbidity of the donor area. Biomaterials represent an alternative for bone restoration. The most widely used compounds are collagen or hydroxyapatite membranes because of their biocompatibility and osteoconductivity. Laser therapy has been applied in comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 40 publications
2
7
0
Order By: Relevance
“…The effect of low-power laser irradiation in bone new formation depends on the intensity, frequency, type and time of application (3). Cunha et al (25) demonstrated that laser with energy density of 5.0 J/cm 2 was not adequate to accelerate the osteogenic process in bone defect regeneration and this was also observed in the present research. On the other hand, an energy density of 7 J/cm 2 showed a significant effect on new bone formation.…”
Section: Discussionsupporting
confidence: 68%
“…The effect of low-power laser irradiation in bone new formation depends on the intensity, frequency, type and time of application (3). Cunha et al (25) demonstrated that laser with energy density of 5.0 J/cm 2 was not adequate to accelerate the osteogenic process in bone defect regeneration and this was also observed in the present research. On the other hand, an energy density of 7 J/cm 2 showed a significant effect on new bone formation.…”
Section: Discussionsupporting
confidence: 68%
“…Additionally, some parameters were calculated from existing data in the articles. It is possible to observe that all studies used infrared laser: six studies used 780 nm, 38,42‐45,48 four used 808 nm, 17,40,49,50 four used 830 nm 22,41,46,47 and 1used 904 nm 39 . Asanami, et al 37 did not inform this parameter on their study.…”
Section: Resultsmentioning
confidence: 95%
“…Among the articles analyzed, only two studies used rabbits as experimental model 37,38 and the others used rats to evaluate the effects of ceramic biomaterial and PBM in bone repair. Furthermore, nine studies performed the bone defect in the tibia of rats, 17,22,39‐45 three studies in the femur, 38,46,47 two studies in the calvaria 48,49 and two studies in the jaw 37,50 . Moreover, it was observed bone defects of distinct sizes of diameter, varying from 0.5 mm 50 to 5 mm 48,49 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations